2020
DOI: 10.3390/ma13041002
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Use of Waste Pig Fat as a Novel Potential Bio-Based Rejuvenator for Recycled Asphalt Pavement

Abstract: This article presents a novel potential bio-based rejuvenator derived from waste pig fat (WPF) for use in recycled asphalt applications. To achieve this purpose, the impact of different doses waste pig fat (e.g., 0, 3, 6, and 9 wt.% WPF) on the reclaimed asphalt pavement binder (RAP-B) performance is investigated. The unmodified and WPF-modified asphalts are characterized by means of Fourier-transform infrared spectroscopy (FT-IR), thin-layer chromatography–flame ionization detection (TLC-FID), scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 33 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…The shift to high temperatures observed in the J4 thermogram could be a consequence of the interactions between the polar compounds of the Jatropha seed shells and the polar fractions of the asphalt, which establish forces that prevent the thermal rupture of bonds at relatively lower temperatures. Similar results were reported by Nciri et al 2020 [33], who reported that more than 6% of waste pig fat improved the thermal stability, which was attributed to the high unsaturated fatty acid content that made the asphalt binder more susceptible to an insignificant thermal decomposition. The thermograms of pistachio-modified asphalt blends with pistachio shells are presented in Figure 8.…”
Section: Thermal Propertiessupporting
confidence: 88%
“…The shift to high temperatures observed in the J4 thermogram could be a consequence of the interactions between the polar compounds of the Jatropha seed shells and the polar fractions of the asphalt, which establish forces that prevent the thermal rupture of bonds at relatively lower temperatures. Similar results were reported by Nciri et al 2020 [33], who reported that more than 6% of waste pig fat improved the thermal stability, which was attributed to the high unsaturated fatty acid content that made the asphalt binder more susceptible to an insignificant thermal decomposition. The thermograms of pistachio-modified asphalt blends with pistachio shells are presented in Figure 8.…”
Section: Thermal Propertiessupporting
confidence: 88%
“…These interactions and related changes in asphalt fractions can be explored through TGA. Nciri et al [20] found that using waste pig fat as a rejuvenator with RAP binders decreased the %R and T onset . Previous studies [21,22] examined the thermal stability of the asphalt binder fractions [saturates, aromatics, resins, and asphaltenes], and it was found that the thermal stability was the highest for asphaltene as the heaviest fraction with the highest molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Various bio-resources, such as waste wood, animal waste [ 4 ], soybean straw [ 5 ] and waste cooking oil, have been identified as suitable for reducing the production of petroleum-based asphalt for the sustainable developments of flexible pavements [ 6 ]. The suitability of bio-resources is a key point for the production and employment of bio-binders, and can be assessed through the FTIR method, which can evaluate the compatibility of a substance or bitumen additive and its structural stability [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%